2009
DOI: 10.1182/blood-2008-12-194704
|View full text |Cite
|
Sign up to set email alerts
|

The favorable impact of CEBPA mutations in patients with acute myeloid leukemia is only observed in the absence of associated cytogenetic abnormalities and FLT3 internal duplication

Abstract: Mutations of the CCAAT/enhancer binding protein alpha (CEBPA) gene have been associated with a favorable outcome in patients with acute myeloid leukemia (AML), but mainly in those with a normal karyotype. Here, we analyzed the impact of associated cytogenetic abnormalities or bad-prognosis fms-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) in 53 patients with CEBPA ؉ de novo AML treated in the Acute Leukemia French Association trials. We found that only those with a normal karyotype and no FLT3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 15 publications
(17 reference statements)
4
50
0
6
Order By: Relevance
“…13 --15 CN-AML with CEBPA mutations define another subgroup of patients also associated with a favorable prognosis. 11,12,16 More recently, several studies have demonstrated that only AML with biallelic CEBPA mutations (most of them being double CEBPA mutations) should be regarded as favorable. 17 --21 Mutations in NPM1, CEBPA and FLT3-ITD allowed a refined prognostic classification of CN-AML and improved risk stratification in this subset of AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…13 --15 CN-AML with CEBPA mutations define another subgroup of patients also associated with a favorable prognosis. 11,12,16 More recently, several studies have demonstrated that only AML with biallelic CEBPA mutations (most of them being double CEBPA mutations) should be regarded as favorable. 17 --21 Mutations in NPM1, CEBPA and FLT3-ITD allowed a refined prognostic classification of CN-AML and improved risk stratification in this subset of AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetically normal AML (CN-AML) represents 40-50 % of all AML cases and currently is considered separate entity in WHO classification [3]. The identification of molecular markers that precisely differentiate a patient's risk could improve treatment outcome and deeply refine the prognosis of patients with CN-AML [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally isolated from rat liver that bound to viral enhancer sequences CCAAT [1,4,5]. CEBPA is the original member of the basic region leucine zipper (bZIP) class of transcription factors [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations